Pengembangan Bahan Ajar Materi Statistika Berbasis Pendidikan Matematika Realistis Indonesia (PMRI) Menggunakan Konteks Wisata Musi Rawas untuk Meningkatkan Pemahaman Siswa SD Negeri 2 Bangun Jaya - Safitri, Catur Indah; Satinem, Yohana; Maharani, Tidi (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to develop a teaching material design based on PMRI (Indonesian Realistic Mathematics Education). It involves testing the validity, practicality, and effectiveness of PMRI-based teaching materials on statistical subjects at SD Negeri 2 Bangun Jaya. This type of research is Research and Development (R&D) with a 4-D development model. The subjects of this study are the fifth-grade students of SD Negeri 2 Bangun Jaya. Data collection techniques include interviews, observations, questionnaires, and tests. Based on validation results from experts, the PMRI-based teaching materials meet the validity criteria with average scores of 0.82 from language experts, 0.93 from content experts, and 0.88 from media experts. The analysis of the practicality assessment sheets from teachers' responses and small group responses indicates that PMRI-based teaching materials meet the practicality criteria, with small group scores averaging 98% (very practical) and teachers' responses averaging 96,87% (very practical). The effectiveness test resulted in an N-gain (g) of 0.77 with a high classification, indicating that the PMRI-based teaching materials have high effectiveness. Based on the research results, it can be concluded that the PMRI-based teaching materials for statistical subjects using the Musi Rawas tourism context are proven to be valid, practical, and effective, making them suitable for use.